Good Corporate Governance: Sebagai Mitigasi Risiko Pelanggaran Etika Terhadap Kinerja Keuangan Perusahaan: Penelitian - Imas Nurani Islami; Irsyad Lukmanul Hakim; Muhamad Syafiq Hilmy; Ahmad Ghossan Abdillah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Good Corporate Governance (GCG) has become a crucial element in preventing ethical violations, particularly in corporate financial reporting. This study aims to analyze the role of GCG as a risk mitigation mechanism for ethical violations and its impact on corporate financial performance. This study uses the Systematic Literature Review (SLR) method by identifying literature relevant to the topic of GCG, which has been published in reputable journals. The results show that effective GCG implementation can increase transparency and accountability, minimize the risk of data manipulation, and improve corporate financial performance in the long term. However, several challenges, such as weak internal controls, an unsupportive organizational culture, and low awareness of the importance of GCG, remain major obstacles in Indonesia. This study also found that integrating GCG with modern technology, such as Enterprise Resource Planning (ERP) systems, can strengthen corporate governance. In conclusion, GCG functions not only as a risk control but also as a strategic tool for creating sustainable governance and supporting business sustainability.